Solar Collectors Based оn Copper Two-Phase Thermosyphons - V. I. Marynenko; V. S. Kulynych (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Thermosyphons and heat pipes offer great opportunities for creating pas sive heat and mass transfer systems. Various design solutions using heat pipes (thermosyphons) in solar energy systems are known. Solar energy is one of the promising energy sources, a step towards reducing dependence on other energy resources. To date, there is already an industrial production of solar collectors based on thermosyphons (heat pipes). In solar collectors, the use of thermosyphons (heat pipes) makes it possible to simplify the assembly of the structure, ensures its high modularity, maintainability and reliability. In the course of research, the authors have developed and justified the design of a solar collector based on thermosyphons fixed on panels that absorb solar rays. In order to analyze the efficiency of the solar collector based on two-phase copper thermosyphons, two models of solar collectors were created, viz. the one with a flat absorbing panel and the one with a cylindrical absorbing panel. The areas of the absorbing surfaces were the same. Both models were studied by the method of thermophysycal experiment. The results of studies of the effectiveness of the above-mentioned solar collectors have been obtained. The efficiency of the solar collector based on a copper two-phase thermosyphon, which is fixed on a cylindrical absorbing panel is 2–5 % more than the efficiency of the solar collector based on a copper two-phase thermosyphon, which is fixed on a flat absorbing panel. The maximum efficiency value obtained at low initial water temperatures for solar collectors with a cylindrical and flat absorbing surface was 60 %.